Soil catenas in a pilot sub-basin in the region of Itajubá, Minas Gerais state, Brazil, for environmental planning - Lima, Olívia de; Melloni, Eliane Guimarães Pereira; Melloni, Rogério; Barison, Marcelo Ribeiro; Curi, Nilton (Semina: Ciências Agrárias, 2021)
Systemic studies that allow the environmental characterization of pilot sub-basins are essential to guide their management, which are the basis for adequate environmental planning. The José Pereira sub-basin has an area of approximately 40 kmÂ² and is located in the municipality of Itajubá, south of the state of Minas Gerais, Brazil. This area was chosen as a pilot sub-basin for this study because it holds an important forest remnant, the Serra dos Toledos Biological Reserve, and part of the urban area of the municipality in the process of expansion, as well as a rural area where inappropriate and intensive agricultural activities are practiced. In this scenario, this atudy examined the soil catenas of this sub-basin to serve as an important instrument of planning for this unit. Eight soil catenas distributed into three topo-morphological compartments were studied. According to the generated soil map, Haplic Cambisols occupy 26% of the sub-basin, in mountainous relief; Red and Red-Yellow Latosols, 6% of the area, predominating in the flat-to-undulating relief; Haplic Gleysols, 7% of the area, in the lowlands, in flat relief and at the footslope. Finally, Red and Red-Yellow Argisols were the predominant classes, occurring in almost 50% of the sub-basin, under undulating and strongly undulating reliefs. Based on the combined results, a model of local evolution of the sub-basin soils was proposed: the younger soils, Haplic Cambisol and Haplic Gleysol, occupy the positions of convex top and floodplain, respectively. In the upper and lower thirds of the landscape, the predominance of Red Argisol is related to constant renewal of soil material, preventing it from reaching the latosolic stage. In addition, part of these Argisols has a Bw horizon below Bt horizon in rugged relief. Moreover, in the landscape lower third, Latosols are present, even in areas with steep slope.